2020
DOI: 10.21203/rs.3.rs-24210/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beyond knowledge acquisition: factors influencing family planning utilization among women in conservative communities in Rural Burundi.

Abstract: Background With a fertility rate of 5.4 children per woman, Burundi has been ranked as seventh highest country with the highest fertility rate in the world. Family planning is known to allow couples to achieve the desired family size, appropriate space birth and the limitation of pregnancies. Also, family planning can contribute to mitigating some health issues such as unintended pregnancies and abortions all of which, are often associated with multi-parity. In conservative community in rural Burundi, knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…Further, injunctive norms highlighted in our study reveal that religious leaders and messages from religious institutions in uence decision-making and perceptions about contraceptive use and family size. This nding aligns with other studies that concluded that there is a relationship between religious condemnation of contraceptives and underutilization of family planning services [22,23].…”
Section: Beliefs About Birth Interval and Family Sizes That Others Ap...supporting
confidence: 90%
“…Further, injunctive norms highlighted in our study reveal that religious leaders and messages from religious institutions in uence decision-making and perceptions about contraceptive use and family size. This nding aligns with other studies that concluded that there is a relationship between religious condemnation of contraceptives and underutilization of family planning services [22,23].…”
Section: Beliefs About Birth Interval and Family Sizes That Others Ap...supporting
confidence: 90%